1988
DOI: 10.1042/bj2500467
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and characterization of the chicken oocyte vitellogenin receptor

Abstract: This paper describes the biochemical characterization of the chicken oocyte plasma-membrane receptor for one of the major lipid-carrying yolk proteins, vitellogenin (VTG). The receptor was extracted from oocyte membranes with the non-ionic detergent octyl-beta-D-glucoside and visualized by ligand blotting, with 125I-VTG as a protein with an apparent Mr of 96000, under non-reducing conditions. It exhibited high affinity for native chicken VTG (Kd 2 X 10(-7) M) but was unable to bind VTG with reductively methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 30 publications
2
58
1
Order By: Relevance
“…In the present study, the same endocytic coated vesicles were found in the oocytes, but only of yellow follicles. On the other hand, Stifani et al (1988) have succeeded in identifying the VTG receptor in chicken oocytes of yellow follicles. Then there might be two different mechanisms for the uptake of nutrients in avian oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the same endocytic coated vesicles were found in the oocytes, but only of yellow follicles. On the other hand, Stifani et al (1988) have succeeded in identifying the VTG receptor in chicken oocytes of yellow follicles. Then there might be two different mechanisms for the uptake of nutrients in avian oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…VLDL was labeled with 125 I to a specific activity of 250 -400 cpm/ng using the iodine monochloride method as described previously (22). Vitellogenin was purified from plasma of estrogen-treated roosters by ion exchange chromatography (DEAE-cellulose) as described (23). Recombinant RAP was produced as a glutathione S-transferase (GST) fusion protein using a pGEX 2T-derived (Pharmacia Biotech Inc.) expression plasmid in DH5␣ bacteria (13).…”
Section: Methodsmentioning
confidence: 99%
“…4444 (Bernardi and Cook, 1960;Stifani et al, 1988;Wallace, 1985). In laying domestic hens (Gallus gallus domesticus), approximately 50% of the liver's daily protein synthesis is attributed to VTG production, potentially tripling the amount of protein in circulation (Gruber, 1972).…”
mentioning
confidence: 99%